GERD PHENOTYPES FROM PH-IMPEDANCE MONITORING PREDICT SYMPTOMATIC OUTCOME ON PROSPECTIVE EVALUATION - Patel, Amit (Neurogastroenterol Motil, 2015)
BACKGROUND: Combinations of reflux parameters (acid exposure time, AET; symptom association probability, SAP) on pH-impedance monitoring describe varying confidence in reflux evidence. We compared outcomes between phenotypes with distinct pre-identified reflux parameters. METHODS: In this observational cohort study, patients undergoing pH-impedance testing over a 5-year period were phenotyped by strength of reflux evidence as strong (abnormal AET, positive SAP), good (abnormal AET, negative SAP), reflux hypersensitivity (RH, normal AET, positive SAP), and equivocal evidence of reflux, and compared to two historical institutional pH monitoring cohorts. Symptom burden (dominant symptom intensity, DSI; global symptom severity, GSS) was assessed by questionnaire at baseline and on prospective follow-up and compared between phenotypes. RESULTS: Of 94 patients tested off PPI therapy, baseline symptom burden was highest with strong reflux evidence and lowest when equivocal (DSI: p=0.01; GSS: p=0.03 across groups). After 3.1±0.2 years follow-up, symptomatic improvement with surgical or medical therapy was highest with strong or good evidence, and lowest when equivocal (DSI: p=0.008; GSS: p=0.005 across groups). This was most pronounced for typical symptoms (DSI: p=0.001; GSS: 0.016 across groups), but not atypical symptoms (DSI: p=0.6; GSS: p=0.2). For testing on PPI therapy, only GSS followed a similar trend (GSS: p=0.057, DSI: p=0.3). Compared to historical cohorts with pH monitoring alone, equivocal evidence for reflux was partly replaced by RH, especially off PPI (p<0.0001). CONCLUSIONS: Phenotyping GERD by strength of reflux evidence on pH-impedance testing off PPI efficiently stratifies symptomatic outcome, especially for typical symptoms, and could be useful in planning management.